PENELITIAN TINDAKAN KELAS PADA MATERI MENULIS DI KELAS VI SD NEGERI 200504 PADANGSIDIMPUAN - -, annahari (CV. Alfa Pustaka, 2024)
This research aims to improve the writing skills of grade VI students of SD 200504 Padangsidimpuan through the Classroom Action Research Method (PTK). Learning to write in grade VI faces challenges such as low motivation and difficulty in compiling structured writing. This research is carried out in three cycles consisting of planning, implementation, observation, and reflection. In the first cycle, learning focuses on basic writing techniques, with 50% of students able to write structured and 60% achieve KKM. The second cycle used a problem-based approach, resulting in improvement, with 75% of students achieving KKM and improvement in writing quality. The third cycle involves collaborative writing, where 90% of students achieve KKM and show improvement in writing skills. Overall, the implementation of PTK with a problem-based and collaborative approach has proven to be effective in improving the writing skills of grade VI students of SD 200504 Padangsidimpuan.